2019
DOI: 10.3390/molecules24091725
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization and Cytotoxicity Assessment towards Human Colon Cancer Cell Lines of Acylated Cycloartane Glycosides from Astragalus boeticus L.

Abstract: In several European countries, especially in Sweden, the seeds of the species Astragalus boeticus L. were widely used as coffee substitutes during the 19th century. Nonetheless, data regarding the phytochemistry and the pharmacological properties of this species are currently extremely limited. Conversely, other species belonging to the Astragalus genus have already been extensively investigated, as they were used for millennia for treating various diseases, including cancer. The current work was addressed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…These characteristics in monodesmosides made them more active than the respective 20,24-epoxycycloartane derivatives. In turn, Graziani et al (2019), suggested that the cytotoxic activity towards Caco-2, HT-29 and HCT-116 cell lines of 20,24-epoxycycloartane saponins could be significantly improved provided some essential structural requirements are met. These include the presence of C3-xylopyranosyl, along with the C6acetoxy group and the C25-free hydroxyl function.…”
Section: Rare Types Of Sapogeninsmentioning
confidence: 99%
“…These characteristics in monodesmosides made them more active than the respective 20,24-epoxycycloartane derivatives. In turn, Graziani et al (2019), suggested that the cytotoxic activity towards Caco-2, HT-29 and HCT-116 cell lines of 20,24-epoxycycloartane saponins could be significantly improved provided some essential structural requirements are met. These include the presence of C3-xylopyranosyl, along with the C6acetoxy group and the C25-free hydroxyl function.…”
Section: Rare Types Of Sapogeninsmentioning
confidence: 99%
“…However, scientists have warned consumers about the aftermath of these synthetic antioxidants on human health because of their carcinogenic effect on human genes 7 . Thus, a recent plethora of works has shown interest in searching for natural antioxidant and anti-proliferative agents to replace chemical synthetics 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…The choice of this plant is justified by its numerous environmental and natural qualities, as well as the fact that it has never been used in wastewater treatment. Furthermore, it is worth noting that this plant is environmentally friendly, as evidenced by its historical use in various fields, including medicine [36,37], and its seeds have been used as a coffee substitute [38]. This plant offers the advantage of providing a safe and environmentally friendly extract for the reduction in and coating of nanoparticles, a crucial step in the preparation of nanoscale materials.…”
Section: Introductionmentioning
confidence: 99%